False dawn : protest, democracy, and violence in the new Middle East - Cook, Steven A. (Oxford university press, 2017)
In False Dawn, noted Middle East regional expert Steven Cook offers a sweeping narrative account of the past five years, moving from Turkey to Tunisia to Yemen to Iraq to Egypt and beyond, ultimately presenting a powerful theoretical analysis of why the Arab Spring failed.